First detection of Zika virus infection in a Croatian traveler returning from Brazil, 2016: Imported Zika virus infection in Croatia - Vilibic-Cavlek, Tatjana; Betica-Radic, Ljiljana; Venturi, Giulietta; Fortuna, Claudia; Djuricic, Stjepan; Salvia-Milos, Antonella; Tabain, Irena; Barbic, Ljubo; Stevanovic, Vladimir; Listes, Eddy; Savini, Giovanni (The Journal of Infection in Developing Countries, 2017)
In the last few years, several imported cases of Zika virus (ZIKV) infection were reported in European countries. We report the first imported ZIKV infection case in a Croatian traveler returning from Brazil. The patient presented with a low-grade fever, pruritic rash, general weakness, myalgia, arthralgia and edema of the legs and recovered completely within a week. ZIKV infection was confirmed by detection of IgM/IgG antibodies using enzyme-linked immunosorbent assay (ELISA) and confirmed by plaque-reduction neutralization test (PRNT). ZIKV IgM antibodies cross-reacted with dengue virus (DENV), West Nile virus (WNV) and tick-borne encephalitis virus (TBEV) in ELISA. In indirect immunofluorescence assay (IFA), IgM cross-reactivity was found only with DENV-3. ZIKV IgG antibodies cross-reacted with DENV in both ELISA and IFA. PRNT for DENV was negative. Control serology performed on days 64 and 98 after disease onset showed a decline in cross-reactive heterologous DENV IgG antibodies compared to persistently high titer of homologous ZIKV IgG antibodies.